(untitled) (Proceedings of International Educators Conference, 2024)
This article explains the importance of the consumption process in the economy. Theories related to consumption in Islamic economy, relationship between consumption and social welfare, factors affecting consumption are revealed. Recommendations on consumption management are provided.